Pengaruh model pembelajaran problem-based learning (PBL) berbantuan media pop-up book terhadap kemampuan berpikir kritis siswa - Devi Kurnia Putri; Kartika Yuni Purwanti (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aimed to determine the effect of the problem-based learning (PBL) learning model assisted by pop up book on students' critical thinking skills. The method used is an experimental design with pre-test and post-test design. The population used in this study was all grade IV students of SD Negeri Gedanganak 03, IVa as a control class and IVb as an experimental class. the data collection techniques used are test techniques and non-test techniques in the form of observation, questionnaires, and documentation. Data analysis techniques use normality tests, homogeneity tests, independent sample t-tests, and regression tests. the results show an influence of the PBL learning model using pop-up book media on students' critical thinking skills as evidenced by tcount = 5.516 > ttable = 3.828 and significant values 0.000 < 0.05. as well as affecting the variable of students' critical thinking ability by 58%, the problem-based learning (PBL) learning model assisted by pop up book media affects the variable of critical thinking ability by 58%. this shows that the problem-based learning (PBL) learning model assisted by Pop Up Book media affects students' critical thinking skills.